S100B and its relation to cerebral oxygenation in neonates and infants undergoing surgery for congenital heart disease. (3rd January 2019) - Hansen, Jan Hinnerk; Kissner, Lydia; Logoteta, Jana; Jung, Olaf; Dütschke, Peter; Attmann, Tim; Scheewe, Jens; Kramer, Hans‐Heiner
Abstract: Objectives: Neonates and infants undergoing surgery for congenital heart disease are at risk for developmental impairment. Hypoxic‐ischemic brain injury might be one contributing factor. We aimed to investigate the perioperative release of the astrocyte protein S100B and its relation to cerebral oxygenation. Methods: Serum S100B was measured before and 0, 12, 24, and 48 hours after surgery. Cerebral oxygen saturation was derived by near‐infrared spectroscopy. S100B reference values based on preoperative samples; concentrations above the 75th percentile were defined as elevated. Patients with elevated S100B at 24 or 48 hours were compared to cases with S100B in the normal range. Neonates (≤28 days) and infants (>28 and ≤365 days) were analyzed separately due to age‐dependent release of S100B. Results: Seventy‐four patients underwent 94 surgical procedures (neonates, n  = 38; infants, n  = 56). S100B concentrations were higher in neonates before and after surgery at all time points ( P  ≤ .015). Highest values were noticed immediately after surgery. Postoperative S100B was elevated after 15 (40.5%) surgeries in neonates. There was no difference in pre‐, intra‐, or postoperative cerebral oxygenation. In infants, postoperative S100B was elevated after 23 (41.8%) procedures. Preoperative cerebral oxygen saturations tended to be lower (53 ± 12% vs 59 ± 12%, P  = .069) and arterial‐cerebral oxygen saturation difference was higher (35 ± 11% vs 28 ± 11%, P  = .018) in infants with elevated postoperative S100B. In the early postoperative course, cerebral oxygen saturation was lower (54 ± 13% vs 63 ± 12%, P  = .011) and arterial‐cerebral oxygen saturation difference was wider (38 ± 11% vs 30 ± 10%, P  = .008). Cerebral oxygen saturation was also lower for the entire postoperative course (62 ± 18% vs 67 ± 9%, P  = .047). Conclusions: Postoperative S100B was elevated in about 40% of neonates and infants undergoing cardiac surgery. Infants with elevated postoperative S100B had impaired perioperative cerebral tissue oxygenation. No relation between S100B and cerebral oxygenation could be demonstrated in neonates.